Inclusive Education Management in the Development of Cognitive Intelligence of Children - Rosyadi BR; Hasan Baharun; Dewi Asiya (STAI Hubbulwathan Duri, 2021)
Early childhood cognitive intelligence that has not been fully developed in inclusive schools needs serious attention, considering that this age is a crucial growth period and the golden age of children. This study aims to analyze and understand inclusive education management in children's cognitive intelligence in RA Al-Iman, and RA Tania. This research uses a qualitative approach with a case study. The data collection technique is done through interviews, observation, and documentation. The data analysis was carried out circularly, starting from the display power, data reduction, and concluding. The results showed that inclusive education in developing children's cognitive intelligence in both institutions was planned and systematic, starting from identifying the needs of inclusive education, designing inclusive education, implementing inclusive education that leads to cognitive intelligence, and assessing inclusive education. This research has implications for the importance of implementing an egalitarian education and refers to equal rights so that children can mingle, play, and get the same education without any differences.